Досягнення і проблеми наукових досліджень, збереження і розвитку архітектурно-містобудівних об`єктів культурної спадщини України - Баланюк, Юліанна; Balaniuk, Juliana (Видавництво Львівської політехніки, 2022)
У статті розкриваються досягнення вітчизняних та зарубіжних науковців у сфері досліджень наукових архітектурно-містобудівних об’єктів культурної спадщини України. Висвітлюються проблеми, викликані значною різницею між набутками теоретичними і реальною практикою збереження та розвитку культурної спадщини у сфері урбаністики й містобудування. Зокрема, гальмування процесів реставрації і пристосування до умов сучасного використання. Встановлено, що за ХХ сторіччя істотно розширилася тематична сфера дослідження міста як феномена культури.

The article reveals the peculiarities of the coverage of the architectural heritage in Ukraine from the historiographical point of view. The theoretical basis of the paper is the work of national and foreign culturologists, urban planners, geo-urbanists etc. During the twentieth century, the thematic sphere of research on the city as a cultural phenomenon has significantly expanded. If in the XIX century the analysis of the urban way of life (both in the city and in the suburbs) was conducted in general from an economic standpoint, in the last century urban culture has been considered in terms of the administrative and economic arrangement, synthesis of social and natural sciences, population of the city centre and suburbs. The literature argues that the architectural forms, structures and decorative plasticity of buildings and structures of the centres of modern Ukrainian cities, belonging to the same functional type, can be different depending on the chronological and geographical parameters. Within one functional type, different types of architectural forms could exist. The architectural form of a building is formed as a set of certain characteristics, depending on the functional program, materials and structures, which can be classified by type, having previously agreed on their terminological characteristics.
Achievements and problems of scientific research, preservation and development of architectural and urban building objects of Ukrainian cultural heritage
Keywords: архітектура; культурна спадщина; містобудування; реставрація; пристосування; урбаністика; architecture; cultural heritage; urban planning; restoration; adaptations; urban planning; 721(477) (045)